a) Phương trình \(14{x^2} - 13x - 27 = 0\)có a - b + c = 14 – (-13) - 27= 0.
Vậy phương trình có hai nghiệm là \({x_1} = - 1\); \({x_2} = - \frac{c}{a} = \frac{{27}}{{14}}\).
b) Phương trình \(5,4{x^2} + 8x + 2,6 = 0\) có a - b + c = 5,4 - 8 + 2,6 = 0.
Vậy phương trình có hai nghiệm là \({x_1} = - 1\); \({x_2} = - \frac{c}{a} = - \frac{{2,6}}{{5,4}} = - \frac{{13}}{{27}}\).
c) Phương trình \(\frac{2}{3}{x^2} + 2x - \frac{8}{3} = 0\)có a + b + c = \(\frac{2}{3} + 2 - \frac{8}{3} = 0\).
Vậy phương trình có hai nghiệm là \({x_1} = 1\); \({x_2} = \frac{c}{a} = - \frac{8}{3}:\frac{2}{3} = - 4\).
d) Phương trình \(3{x^2} - (3 + \sqrt 5 )x + \sqrt 5 = 0\) có a + b + c = \(3 - (3 + \sqrt 5 ) + \sqrt 5 = 0\).
Vậy phương trình có hai nghiệm là \({x_1} = 1\); \({x_2} = \frac{c}{a} = \frac{{\sqrt 5 }}{3}\).